Defining and measuring acceptability of surgical interventions: A scoping review - Sophie James; Jennie Lister; Joy Adamson; Catherine Hewitt; Antonina Yakimova; Andrew Mott; Helen Fulbright; Catriona McDaid (PLoS ONE, 2025)
Background Acceptability, in the context of healthcare interventions is a frequently used term, including in evaluations of surgical interventions. This reflects the importance of the concept to all stakeholders and significance to designing, implementing and evaluating interventions. Despite this, definitions and measurement of acceptability are not standardised, and acceptability is often poorly conceptualised. The aim of this scoping review was to identify how studies define, measure and report the acceptability of a surgical intervention. Methods A scoping review was conducted adhering to the Joanna Briggs Institute guidelines and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. A comprehensive search of MEDLINE; Embase:APA PsycInfo; EBHealth-KSR Evidence; Cochrane Central Register of Controlled Trials; International HTA database; ClinicalTrials.gov and WHO International Clinical Trials Registry Platform was conducted for the period January 2000 to November 2023. No language limits were applied. Results Sixty-seven studies from 25 countries were included. The majority of studies (n = 60; 90%) did not provide a definition of acceptability. Various methods were used to collect data on acceptability, most frequently a questionnaire (n = 36; 54%), followed by qualitative interviews (n = 16; 24%). Thirty-three studies (49%) reported acceptability of the surgical intervention received to patients, nine (13%) reported hypothetical acceptability of the surgical intervention to patients, four (6%) reported acceptability to both patients and surgeons, and four studies (6%) the acceptability to surgeons alone. Conclusion Studies assessing acceptability of a surgical intervention tended not to provide a definition of acceptability and demonstrated a lack of clarity in the use of acceptability in the context of surgical interventions. There was substantial variability in how and when acceptability was measured and from which perspective. Further research is required to explore the most appropriate approaches to address variability and promote a more consistent conceptualisation and accurate measurement of acceptability in evaluations of surgical interventions.